A process and temperature robust constant-gm input/output rail-to-rail op-amp. Issue 6 (June 2015) - Shahpari, Nima; Dehghani, Rasul; Rabani, Payam
Abstract A rail-to-rail operational amplifier is designed with minimum variation in the input stage transconductance (<alternatives><inline-graphic xlink:href="ark:/27927/pgj24fgqfcd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />gm</alternatives>) in standard <alternatives><inline-graphic xlink:href="ark:/27927/pgj24fgq4pq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.18μm</alternatives> CMOS technology. In this design, transconductance is maintained approximately constant independent of the operation region of the input transistors (i.e., saturation or weak inversion regions). Unlike conventional methods in rail-to-rail designs in which two complementary differential pairs are used, in this work, by using a single input pair, the sensitivity to mismatches between PMOS and NMOS input transistors is eliminated. A Monte-Carlo simulation with n=300 was run to ensure mismatch insensitivity. Simulation results show that the input stage transconductance deviation as the input common-mode voltage varies from rail-to-rail is less than ±<alternatives><inline-graphic xlink:href="ark:/27927/pgj24fgr5rt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.81%, </alternatives> in typical conditions and at 27 °C. When the temperature varies from −20 °C to 120 °C, the variation does not exceed ±1.28%. Furthermore, the variations of <alternatives><inline-graphic xlink:href="ark:/27927/pgj24fgr4x2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />gm</alternatives> in two long-channel (L=1 µm) and short-channel (L=0.18 µm) cases are ±0.85% and ±0.9%, respectively. This proves that the introduced circuit works properly regardless of the channel length of the input pair.